Significance of Chromosome 9p Status in Renal Cell Carcinoma: A Systematic Review and Quality of the Reported Studies. (30th April 2014) - El-Mokadem, Ismail; Fitzpatrick, John; Rai, Bhavan; Cunningham, J.; Pratt, Norman; Fleming, Stewart; Nabi, Ghulam
Abstract : Defining the prognosis of renal cell carcinoma (RCC) using genetic tests is an evolving area. The prognostic significance of 9p status in RCC, although described in the literature, remains underutilised in clinical practice. The study explored the causes of this translational gap. A systematic review on the significance of 9p status in RCC was performed to assess its clinical applicability and impact on clinical decision-making. Medline, Embase, and other electronic searches were made for studies reporting on 9p status in RCC. We collected data on: genetic techniques, pathological parameters, clinical outcomes, and completeness of follow-up assessment. Eleven studies reporting on 1, 431 patients using different genetic techniques were included. The most commonly used genetic technique for the assessment of 9p status in RCC was fluorescence in situ hybridization. Combined genomic hybridisation (CGH), microsatellite analysis, karyotyping, and sequencing were other reported techniques. Various thresholds and cut-off values were used for the diagnosis of 9p deletion in different studies. Standardization, interobserver agreement, and consensus on the interpretation of test remained poor. The studies lacked validation and had high risk of bias and poor clinical applicability as assessed by two independent reviewers using a modified quality assessment tool. Further protocol driven studies with standardised methodology including use of appropriate positive and negative controls, assessment of interobserver variations, and evidenced based follow-up protocols are needed to clarify the role of 9p status in predicting oncological outcomes in renal cell cancer.